Analysis of Ukraine border-region economic collaboration effectiveness on the example of Sumy region and place of marketing of innovations in it - S.М. Мakhnusha; V.М. Оliynyk; S.М. Frolov (Marketing i Menedžment Innovacij, 2013)
The aim of the article. The authors analyze the spheres of general interests and collaboration between Ukraine and Russia and methodical bases of such collaboration and its instruments in the article. The analysis of dynamics of external trade turnover and commodity structure of export and import of Sumy region as displays of economic border-region collaboration of two states is carried out. Forecast models of Sumy region commodities and services external trade are built. Place and importance of economic collaboration of two states on principles of innovations are found out. The process of marketing of innovations and its role in providing effectiveness of border-region economic collaboration is characterized.The results of the analysis. Collaboration in economic sphere with Russia is one of foreground jobs of Ukraine. Both of the states remain largely mutually dependent from the resource and technological points of view, have the ramified network of multilateral economic connections, and aspire to the civilized integration in outer economic space.The features of global and national development need from Ukraine and Russia forming of the relations in a strategic prospect exactly on economic foundation, maximally using an interregional collaboration in which the special role is played by border-region territories first of all, carrying out the role of buffer between countries. The most developed and often used instrument of economic border-region collaboration between Russia and Ukraine are export-import operations.Sumy region is very dependent upon external economic relations, as basis of its GDP is made by export-import operations that are typical for border-region territory. The Russian Federation is the general economic partner of Sumy region, thus at the years its role grows only. On the whole, it is possible to draw to the conclusion about predominant export commodity orientation of Sumy region border collaboration with the countries of the UIS, in thereby with Russia. As the built prognosis testifies, the export of commodities will grow at the years, in particular the export of commodities will grow mainly to the countries of the UIS, in thereby to Russia.In relation to the import of commodities: its volume is less, by comparison to an export, but a tendency is expected to its increase.What touches a situation with the export of services, then its volume considerably is less (and more close connection is traced with the countries of the UIS, in thereby with Russia) than the volume of commodity operations, and a tendency to reduction of this index is expected.Speaking about efficiency of economic border-region collaboration of Sumy region with Russia and taking into account its substantial commodity export orientation (in particular in such categories of commodities, that suppose ability of realization of innovational potential and scientific-technical achievements in industries), it should be noted that all of these additionally actualizes an importance of problem of marketing of innovations in providing the efficiency of border-region economic collaboration and desirable effectiveness of commodity export operations with the innovation products.As an analysis of efficiency of economic border-region collaboration of Sumy region and Russia showed, it is mainly export oriented, in particular export of commodities of such basic groups as chemical industry and the industries related to it, mechanical equipment; machines and mechanisms, electronic equipment and its parts; devices.Conclusions and directions of further researches. Exactly in the production of these commodities realization of innovative potential of the state and increase of competitiveness of its commodities becomes possible at the foreign trade market. The effective events of marketing of such innovations must promote efficiency of Sumy region economic collaboration with border territories, in particular with Russia.It should be noted that such problems are present as:it is reduction of demand on products that present the principal items of mutual export and import as a result of braking of rates of the economy growing in both countries;it is the considerable rising in price of import as a result of high inflation and rapid devaluation of national currency, that is especially perceived in Ukraine;it is a risk of introduction from the side of Russian Federation government of additional access of the Ukrainian products restrictions to the Russian market with the aim to support a national economy in crisis terms.The prospect of further research is an efficiency of marketing events estimation during realization of economic collaboration of Sumy region with border territories.